Answer:
A theorem stating that the square of the length of the hypotenuse of a right triangle is equal to the sum of the squares of the lengths of the other sides. It is mathematically stated as c2 = a2 + b2, where c is the length of the hypotenuse and a and b the lengths of the other two sides.
Step-by-step explanation:
You said X = (5y+1) / (y-2)
Multiply each side by (y-2):
X(y-2) = (5y+1)
Eliminate parentheses:
Xy - 2X = 5y + 1
Add 2X to each side:
Xy = 5y + 1 + 2X
Subtract 5y from each side:
(X-5)y = 1 + 2X
Divide each side by (X-5):
<em>y = (1+2X) / (X-5) </em>
Answer:
2x+20 + x+40 = 180
Step-by-step explanation:
The angles are supplementary so they add to 180
2x+20 + x+40 = 180
Answer:
+6 B
Step-by-step explanation:
Which of the following completes the rule for this translation, (x, y) + (x + 6, )?
Answer:
yes
Step-by-step explanation:
yes that is true you are correct